Preparation and characterization of a metered dose transdermal spray for testosterone - Wangding Lu; Huafei Luo; Yubo Wu; Zhuangzhi Zhu; Hao Wang (Acta Pharmaceutica Sinica B, 2013)
The objective of the present work was to develop a metered dose transdermal spray (MDTS) formulation for transdermal delivery of testosterone and to characterize its efficacy. Testosterone release from a series of formulations was assessed in vitro. Skin from hairless mice was used in permeation experiments with Franz diffusion cells. The spray pattern, pump seal efficiency, average weight per metered dose and dose uniformity were evaluated. An optimized formulation containing 10% (w/v) testosterone, 9% (v/v) azone and 91% (v/v) ethanol was based on good skin permeation and acceptable drug concentration and permeation enhancer (PE) content. A skin irritation study indicated that the formulation was non-irritating in a rat model. An in vivo pharmacokinetic study indicated that the optimized formulation showed a different plasma concentration-time profile from that of the commercially available product Testopatch®. The Testopatch® product demonstrated a more sustainable drug release. The evaluation of the testosterone MDTS indicated that it could deliver reproducible amounts of the formulation per actuation. The results obtained showed that the MDTS is a potential alternative therapeutic system for transdermal testosterone delivery.